Cell wall degradation of outeloua repens in vitro by pure cultures of R. Flavefaciens and F. succinogenes isolate from cattle grazing tropical lowland pastures in Colombia - Oáa, F.=700 1 Arcos, M.; Diaz, T.E.; Pittroff, W.
(En, Es)
ilus., 40 ref.
Keywords: GRAMINEAS FORRAJERAS; BOUTELOUA; DEGRADACION; ENZIMAS; INOCULACION; RUMINOCCOCUS; LIGNOCELULOSA; COLOMBIA